2023
DOI: 10.1099/mic.0.001383
|View full text |Cite
|
Sign up to set email alerts
|

Microbe Profile: Ruminococcus gnavus: the yin and yang of human gut symbionts

Nathalie Juge

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…However, with the advancement of sequencing technology, studies have shown that species within the genus Ruminococcus belong to two bacterial families: Ruminococcaceae and Lachnospiraceae [ 29 ]. Some of these bacteria, such as Ruminococcus gnavus , have been shown to be associated with various intestinal and extraintestinal diseases and are increased in abundance in inflammatory bowel disease and metabolic diseases [ 30 , 31 , 32 ]. Unfortunately, limited by the accuracy of 16s analysis, the experiments were unable to explore the impact of Salmonella Typhimurium infection on duck intestinal microbiota at the species level.…”
Section: Discussionmentioning
confidence: 99%
“…However, with the advancement of sequencing technology, studies have shown that species within the genus Ruminococcus belong to two bacterial families: Ruminococcaceae and Lachnospiraceae [ 29 ]. Some of these bacteria, such as Ruminococcus gnavus , have been shown to be associated with various intestinal and extraintestinal diseases and are increased in abundance in inflammatory bowel disease and metabolic diseases [ 30 , 31 , 32 ]. Unfortunately, limited by the accuracy of 16s analysis, the experiments were unable to explore the impact of Salmonella Typhimurium infection on duck intestinal microbiota at the species level.…”
Section: Discussionmentioning
confidence: 99%
“…Ruminococcus is a common bacterium in the feces of ruminants, mainly colonizing the jejunum and ileum of the intestinal lumen ( Guerra et al, 2022 ; Zhang et al, 2022 ), and is involved in the degradation of starch and other complex polysaccharides ( Rangarajan et al, 2022 ). Ruminococcus has also been well-documented as an inducer of active inflammation in animals ( Hall et al, 2017 ; Henke et al, 2021 ), and has been shown to play a role in the maintenance of homeostasis by acting as a key symbiotic component of the intestinal ecosystem ( La Reau and Suen, 2018 ; Crost et al, 2023 ; Juge, 2023 ). Paeniclostridium is a pathogenic bacterium ( DeCandia et al, 2023 ) that induces inflammation in the intestinal tract and in various tissues in animals ( Nyaoke et al, 2020 ; Gryaznova et al, 2021 ), via its ability to produce cytotoxic endotoxins ( Watts et al, 2019 ; Li et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…It belongs to the Firmicutes, it is also a member of the family Lachnospiraceae. An increasing number of enteric and extra-enteric diseases are associated with this bacterium [ 61 ]. Zhi-ying Song [ 4 ] and Yao Su [ 36 ] found that g-Ruminococcus was a characteristic biomarker for the normal pregnant women group and Ruminococcaceae_UCG014 was a characteristic biomarker for the GDM-only group, respectively.…”
Section: Relationship Between Intestinal Microbiome and Gdmmentioning
confidence: 99%